The Wiley-Blackwell handbook of schema therapy : theory, research, and practice - Vreeswijk, Michiel van; Broersen, Jenny; Nadort, Marjon (Chichester, West Sussex, UK : Wiley-Blackwell, a John Wiley & Sons, Ltd., Publication, 2012)
The Wiley-Blackwell Handbook of Schema Therapy provides a comprehensive overview of developments in the theory, diagnosis, treatment, research, implementation, and management of schema therapy. Presents the first comprehensive overview of schema therapy - goes far beyond all previous books on the subject to cover theoretical, research and practical perspectivesCovers the latest developments, including work on mindfulness and borderline personality disorder, as well as new applications of schema therapy beyond personality disordersIncludes chapters by leaders in the field including Wendy Behary.
Part V: The therapist: training, supervision and self-care in schema therapy. Training for and registrations of Schema therapists -- Training and supervision in schema therapy -- The Schema Mode Model in personal therapy -- Therapist self-care in the context of limited reparenting -- Part VI: Research in schema therapy. Effectiveness studies -- Experimental studies of schema modes -- Experimental studies for schemas -- Validation of the Young Schema Questionnaire -- Validation of the Schema Mode Inventory -- Part VII: Implementation and public relations in schema therapy. Implementation of schema therapy in general mental healthcare institutes -- Using ST principles to increase the therapeutic efficacy of the forensic care team's interactions with personality disordered clients -- Implementation of schema therapy in de Rooyse Wissel Forensic Psychiatric Center -- Cost-effectiveness of schema therapy -- Public relations for schema therapy -- Concluding thoughts.
Includes bibliographical references and indexes.
Online resource; title from electronic title page (ebrary, viewed on August 11, 2015).
Keywords: Schema-focused cognitive therapy; Personality disorders -- Patients -- Treatment; Cognitive Therapy -- methods; Mental Disorders -- therapy; Schema-focused -- Handbooks, manuals, etc; Medicine; PSYCHOLOGY -- Psychotherapy -- General; Schema-focused cognitive therapy; Schemas (Psychology); Kognitiv beteendeterapi; Kognitiv terapi; Personlighetsstörningar.; Electronic books; Handbooks and manuals